2020
DOI: 10.1002/pca.2977
|View full text |Cite
|
Sign up to set email alerts
|

MS diagnostic model and rapid distinguishing of bioactive limonoids in fruits of Melia toosendan using solid‐phase extraction coupled with LC–MS/MS

Abstract: Introduction Melia toosendan Sieb. et Zucc. has been used as a Chinese folk medicine for roundworm treatment since ancient times. Many diverse limonoids have been isolated from Meliaceae plants, but it remains difficult to isolate and identify other limonoids because of their small natural concentrations. Objective This study was performed to overcome the difficulties associated with fast and accurate identification of limonoids and establish a reliable and sensitive method for the analysis of minor limonoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The chief sources of limonoids are the Meliaceae and Rutaceae plant families (Da Silva et al 1984; Fig. 1 Basic limonoid skeleton Champagne et al 1992;Roy and Saraf 2006;Liao et al 2009;Fang et al 2011;Sun et al 2018;Sartor et al 2019;Cui et al 2021;Luo et al 2022) but they also can be found very occasionally in Cneoracea and Ptaeroxylaceae families and Harrisonia spp. of Simaroubaceae (Ourison et al 1964;Connolly 1983;Da Silva et al 1987;Tundis et al 2014;Amit and Shailendra 2006;Tan and Luo 2011).…”
Section: Natural Sources Of Degraded Limonoidsmentioning
confidence: 99%
“…The chief sources of limonoids are the Meliaceae and Rutaceae plant families (Da Silva et al 1984; Fig. 1 Basic limonoid skeleton Champagne et al 1992;Roy and Saraf 2006;Liao et al 2009;Fang et al 2011;Sun et al 2018;Sartor et al 2019;Cui et al 2021;Luo et al 2022) but they also can be found very occasionally in Cneoracea and Ptaeroxylaceae families and Harrisonia spp. of Simaroubaceae (Ourison et al 1964;Connolly 1983;Da Silva et al 1987;Tundis et al 2014;Amit and Shailendra 2006;Tan and Luo 2011).…”
Section: Natural Sources Of Degraded Limonoidsmentioning
confidence: 99%
“…Even if the min pairs cos was set as 0.4, under which the clustered nodes were unreliable, the standards were still desolate (Figures S5–S7). Thus, Sephadex LH-20 gel was used to remove impurities and yielded Fr.c3-c to increase the intensity of targeted precursor ions and decrease the noise ions in MS/MS , for MN analysis. On the basis of the results of single-node-based molecular networking analysis of Fr.c3, the MN of Fr.c3-c was generated with a min pairs cos of 0.6 (Figure S8), and there was only one red triquetrous node ( m / z 404.24) clustered with the lindenane heterodimer standards (Figure ).…”
mentioning
confidence: 99%